Influence of Portland cement on performance of fine rice husk ash geopolymer concrete: Strength and permeability properties. (20th September 2021) - Saloni,; Parveen,; Yan Lim, Yee; Pham, Thong M.
Highlights: FRHA was partially replaced by OPC in GPC. Strength and durability properties were studied. Optimum performance was noticed at 15% substitution. Dense microstructure was achieved due to additional calcium products. Abstract: Recently, industrial by-products such as rice husk ash has been identified as potential alternative binders to Ordinary Portland Cement (OPC) in concrete. Yet, it compromises the strength and concrete performance to some extent. One viable way is through partial replacement of such alternative binders with OPC, in order to achieve satisfactory concrete properties for practical applications. Thus far, no thorough study has been conducted to understand the properties of fine rice husk ash (FRHA) based geopolymer concrete (GPC) with different OPC content. This study focused on the influence of OPC as a substitution of FRHA on the strength and permeability of FRHA based GPC. The effects of OPC substitution on various properties, namely compressive strength, flexural strength, splitting tensile strength, modulus of elasticity, water absorption and chloride penetration resistance, were experimentally studied. Scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD) techniques were also conducted to analyse the microstructural features. Experimentally, the optimum content of OPC in GPC was identified as 15%, since the highest compressive strength of 53.69 MPa was achieved at 90 days. Deterioration of the mechanical properties was observed with further increase in OPC replacement. Flexural strength, splitting tensile strength and modulus of elasticity also followed similar trends. In addition, water absorption (4.42%) and charge (1037 Coulombs) achieved by specimens with 15% OPC replacement were the lowest for all ages, suggesting improved durability performance. Microstructural studies also showed the enhanced and denser structure of GPC due to OPC substitution as a result of the formation of higher amount of calcium-silicate-hydrate (CSH) gel alongside calcium-aluminate-silicate-hydrate (CASH) and sodium-aluminate-silicate-hydrate (NASH) gels. These polymerisation gels strengthened the network by filling the voids and enhancing the properties of GPC. Thus, it was concluded that the optimal combination of FRHA (85%) and OPC (15%) prominently enhanced the GPC properties by improving its overall performance.